IMAGE OF AN INTEREST-RELATED EDUCATION TEACHER: PERSPECTIVES FROM HEADS OF EDUCATION INSTITUTIONS - Pavlovs, Māris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
This article analyses the professional and personal qualities of interest-related education teachers, their impact on students and relationships with students, based on the results of a survey of 178 heads of educational institutions. The findings reveal that most heads believe that teachers are usually accurate and timely in their actions, build good relationships with students, and are not too harsh with them. In addition, the heads of the institutions are aware of the potential problems in the learning process and are ready to address these problems. These conclusions reflect the important role of interest-related education teachers in the learning process and point to the need to further develop teachers’ professional and personal qualities in order to ensure an effective learning environment and student development.